Development of the MRB 201/301 - Marshall, A. G. (The International Hydrographic Review, 2015)
The early history of navigation and hydrographic survey aids leading to the invention of the first Tellurometer and the MRB2 Hydrodist is briefly described. The various operational and technical factors which influenced the design concept of the later MRB201 are discussed, together with actual field results obtained with the equipment. Some results of trials with the high speed MRB301 are also tabulated.